CD147 expression as a clinicopathological and prognostic indicator in breast cancer: a meta-analysis and bioinformatics analysis - Shuai Shi; Hong-Yan Ma; Yin-zhou Sang; Ying-bo Ju; Xing-guang Wang; Zhi-Gang Zhang (BMC Cancer)
Abstract Background CD147 belongs to the immunoglobulin superfamily, also known as Basigin (BSG), and is a highly glycosylated single transmembrane glycoprotein present in various tissues. Meta and bioinformatic analyses were used to explore the correlation between CD147 expression and the clinicopathological characteristics prognosis of breast cancer. Method Literature related to breast cancer was retrieved through PubMed and CNKI databases, and a meta-analysis was conducted using Review Manager 5.2 software. Results The meta-analysis revealed that all articles included data on 522 patients with breast cancer and 492 normal tissues. CD147 expression in breast cancer tissue was higher compared to that in normal tissue([8.92–139.52]; p < 0.00001 I2 = 80%) and negatively correlated with LM, clinical stage, histological grade, and ER positive expression. Bioinformatic analysis revealed that the expression of CD147 in breast cancer tissue was higher than that in normal tissue, and its high expression was closely related to the clinicopathological characteristics of patients, such as LM, histological grading, and clinical staging. According to the TIMER database, CD147 expression was closely related to immune cell infiltration in breast cancer. Conclusion These results indicated that high CD147 expression might be closely linked to the occurrence as well as the development of breast cancer, and can function as a good indicator of prognosis in the future, providing new methods and ideas for the prevention and treatment of breast cancer.